Implementasi Diagnosis Organisasi pada Perguruan Tinggi Swasta (PTS) di Kota Jambi - Jonner Simarmata; Said Almaududi (Universitas Batanghari, 2019)
Organizational effectiveness positively impacts sustainability and competitiveness of organizations. Higher Education is no exception. To gain sustainability and effectiveness of organizations, diagnosis should be implemented regularly. In theory, organizations that implement diagnosis regularly have sustainable competitiveness. Today, Higher Educations face tough competition due to many factors suchs as globalization, technological advancement, and rapid demographic changes. This current research aims at implementing organizational diagnosis on Private Higher Educations (PHEs) in Jambi City. Specifically, the purpose of this diagnosis is to know how effective is the organizations in terms of purpose, structure, leadership, relationship, rewards, mechanism, attitutde toward changes, and learning practices. For this purpose, a set of questionaires were distributed to respondents who were cluster-randomly selected from four institutions. Data analysis shows that in general higher education organization in Jambi City is considered sufficiently effective. This suggests that improvement should be made. In particular, there are three organizational aspects that respondents give the lowest score. They are reward system, attitude toward changes, and learning practices. This means that these three variabels should be given more attention by top managers.